Suppressing the Ring Stain Effect with Superhydrophilic/Superhydrophobic Patterned Surfaces - Yin, Qiming (ACS Omega, 2020)
[Image: see text] The ring stain phenomenon is a critical hindrance to the distribution of the solute during drying for biochemical assays and materials deposition. Herein, we developed a substrate, characterized with hydrophilic spots surrounded by hydrophobic areas, to suppress the ring stain effect, and fabricated four kinds of patterned surfaces to investigate the relationship between the surface free energy and ring-suppressing performance. We found that during the evaporation process, a drop was constrained on the hydrophilic spot with a pinned contact line, and the ring stain effect was suppressed significantly. The suppressing performance of the ring stain effect increases with surface free energy differences between the hydrophilic and hydrophobic regions.